The Change in Neutrophil-to-lymphocyte Ratio after Initiation of Nivolumab Monotherapy May be a Strong Marker of Response and Predictor of Prognosis in Advanced Non-small Cell Lung Carcinoma - Murata, Saori; Nakamura, Morio; Sugihara, Kai; Sakai, Tetsuya; Ishioka, Kota; Takahashi, Saeko; Sasada, Shinji; Yasuda, Hiroyuki; Fukunaga, Koichi (Asian Pacific Journal of Cancer Care, 2022)
Background: The neutrophil-to-lymphocyte ratio (NLR) is recognized as a predictive and prognostic biomarker in various malignancies. We investigated the utility of the NLR in patients with advanced non-small cell lung cancer (NSCLC) in the early phase of nivolumab monotherapy. Methods: Thirty-one patients with advanced NSCLC were treated with nivolumab monotherapy from January 2016 to August 2017. They underwent the first response evaluation 8.3±3.3 weeks (mean±SD) after 3.8±1.8 times of administration. The NLR values at baseline (NLR/base) and at the first response evaluation (NLR/1st) were analyzed to evaluate for the association between NLR and the following parameters: treatment response, progression-free survival (PFS) and overall survival (OS). Results: The median follow-up period was 467 days (range: 38-1903 days). NLR/1st in the disease control (DC) group (n=21, median: 4.36, range: 0.82-11.3) was significantly lower than that in the progression disease (PD) group (n=10, median: 11.91, range 2.04-31.00) (p<0.01). The median PFS and OS for all patients were 184 and 540 days, respectively. A higher NLR/1st resulted in a worse DC rate (OR 0.78, p<0.05), and was associated with shorter PFS (HR 1.11, p<0.005) and OS (HR 1.12, p<0.0005). A greater increase in NLR, from NLR/base to NLR/1st was associated with shorter PFS (HR 2.04, p<0.01) and OS (HR 1.66, p<0.05). Conclusions: In NSCLC patients receiving nivolumab monotherapy, elevated NLR at the first response evaluation and its inclined change from baseline could be significantly stronger markers of poor response and predictors of worse prognosis than NLR at baseline.